Pemanfaatan Media Kaligrafi pada Mata Pelajaran PAI Materi Asmaul Husna untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar - Rizqiyah, Nailatur; Syarif, Zainuddin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The utilization of innovative learning media is one of the keys in increasing students' interest in learning, especially in Islamic Religious Education (PAI) subjects. This research is motivated by the need to explore the effectiveness of calligraphy media in teaching Asmaul Husna material at the elementary school level. The purpose of this research is to find out the strategy of utilizing calligraphy media in increasing students' interest in learning and identifying its advantages and challenges. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation at SDN Gunung Sekar 2 Sampang. The results showed that calligraphy media is effective in attracting students' attention, increasing active participation, and fostering sustainable interest in learning. The strategies used include imitating and creating calligraphy independently, which builds students' cognitive, affective and motor aspects. Although there are challenges such as differences in students' abilities and limited tools, teachers are able to overcome them through adaptive approaches. The implications of this study emphasize the importance of art integration in religious education to create fun and meaningful learning.